Hypocrisy or maturity? Culture and context differentiation - Matsumoto, David (2009)
We introduce a new construct called Context Differentiation (CD), and describe how it functions on both the individual and cultural levels. We derive several measures of it from a multi-context measure of cultural display rules for emotional expressions obtained from 33 countries, and examine country and cultural differences on it, and relate those differences to cultural value dimensions associated with context. Findings indicated that cultures were reliably associated with measures of CD. The framework and findings provide a platform for new research in the future examining how individuals differentiate their behaviours across contexts, and how cultures facilitate that differentiation.